2009
DOI: 10.1063/1.3123803
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of metal mixed plastic superconductors: Electrical properties of tin-antimony thin films on plastic substrates

Abstract: Metal mixed polymers are a cheap and effective way to produce flexible metals and superconductors. As part of an on-going effort to learn how to tune the properties of these systems with ion implantation, we present a study of the electrical properties of these systems prior to metal-mixing. We show that the electrical properties of tin-antimony thin films are remarkably robust to variations in the substrate morphology. We demonstrate that the optical absorbance of the films at a fixed wavelength provides a re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 33 publications
(47 reference statements)
1
9
0
Order By: Relevance
“…That said, we expect the coupling to be dependent on the nature of the carbonized polymer matrix created by the ion beam, 28 which fills the space between the grains, as well as the size distribution and morphology of the grains themselves. However, on the weight of evidence presented here and in our earlier work, 13,15 it is clear that this material system is granular.…”
Section: B Crossing Over To the Insulating Sidementioning
confidence: 68%
See 3 more Smart Citations
“…That said, we expect the coupling to be dependent on the nature of the carbonized polymer matrix created by the ion beam, 28 which fills the space between the grains, as well as the size distribution and morphology of the grains themselves. However, on the weight of evidence presented here and in our earlier work, 13,15 it is clear that this material system is granular.…”
Section: B Crossing Over To the Insulating Sidementioning
confidence: 68%
“…The first is the preimplant metal thickness because it provides the easiest control over the conductivity, even though this can be a slightly difficult parameter to control with precision. 15 The second is the implant temperature, which we believe provides some control over the disorder of the resulting film, as we will show in the next section. A more extensive study of the role of the fabrication and ion-implantation parameters in determining the sample conductivity will be the subject of a separate, forthcoming paper.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the conductivity can be controlled by the pre-implant metal thickness, we have recently shown that doing so gives inhomogeneous films with anisotropic electrical properties as the metal thickness and resulting conductivity are reduced. [14,15] Herein, we demonstrate that a much more effective route to achieving tunability in metal-mixed polymers is to harness the same sputtering process that limits the conductivity when using a metal ion beam to implant native polymer films. [10] Metal mixing with a heavier element ion beam enhances the sputtering, allowing one to start with a thicker metal layer, and achieve more uniform and precise control over the metal content and the resulting film's electrical properties.…”
mentioning
confidence: 97%